THE EFFECT OF LIQUIDITY, PROFITABILITY, AND A SIZE OF A COMPANY ON THE FIRM VALUE OF THE FOOD AND BEVERAGE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE BEFORE AND DURING THE COVID 19 PANDEMIC. - Suci Fiqiah Kirana ,; Nekky Rahmiyati, (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This research aims to examine the effect of liquidity, profitability, and a size of a company on the firm value of the food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) before and during the Covid-19 pandemic. The method of determining the sample using purposive sampling. Research data is secondary data. The data analysis technique used in this study is multiple linear regression analysis using SPSS 26. The results of this study are that liquidity has an insignificant effect on the value of food and beverage companies before and during the Covid-19 pandemic, profitability has a significant effect on the value of food and beverage companies before and during the Covid-19 pandemic, a size of a company had an insignificant and significant negative effect on the firm value of food and beverage companies before and during the Covid-19 pandemic, liquidity, profitability, and a size of a company simultaneously had a significant effect on the firm value of food and beverage companies before and during the Covid-19 pandemic.